2023
DOI: 10.1111/srt.13473
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and acne: A Mendelian randomization study

Qiurui Cao,
Jinyan Guo,
Shuangqing Chang
et al.

Abstract: BackgroundPrior observational studies have identified a relationship between the composition of gut microbiota and the onset of acne. To ascertain the causal relationship underlying this association, we adopted the Mendelian randomization (MR) method, which offers a powerful approach to causal inference.MethodsSummary statistics on gut microbiota and acne were obtained from the MiBioGen and FinnGen consortium, respectively. The causal relationship was assessed using multiple methods in a two‐sample framework, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Furthermore, four other types of gut microflora, including those from the Candidatus soleaferrea group and Eubacterium coprostanoligenes showed suggestive protective effects against acne. In contrast, Allisonella and Bacteroides were responsible for exacerbating acne [122].…”
Section: Acnementioning
confidence: 98%
“…Furthermore, four other types of gut microflora, including those from the Candidatus soleaferrea group and Eubacterium coprostanoligenes showed suggestive protective effects against acne. In contrast, Allisonella and Bacteroides were responsible for exacerbating acne [122].…”
Section: Acnementioning
confidence: 98%
“…This axis suggests a close relationship between gut health and skin health, indicating that the microbiota and metabolites in the gut can affect skin conditions through various pathways 9 . Research has already demonstrated that certain gut microbiota are closely associated with facial skin aging and acne 10,11 . Additionally, studies have shown that inflammatory bowel disease and psoriasis may influence each other through shared genetic mechanisms and tissue expression pathways 12 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Research has already demonstrated that certain gut microbiota are closely associated with facial skin aging and acne. 10,11 Additionally, studies have shown that inflammatory bowel disease and psoriasis may influence each other through shared genetic mechanisms and tissue expression pathways. 12 However, the relationship between the gut microbiota and the skin microbiota still requires further investigation.…”
mentioning
confidence: 99%
“…The relationship between alcohol consumption and Rosacea is also debated, with some studies suggesting an association, 8,18 while others find no significant difference 19 . Studies have shown that cigarette smoking and drinking can affect the human microbiome, 20,21 and changes in skin microbiome and intestinal microbiome are closely related to the occurrence and development of Rosacea 22–24 . Effective treatment interventions targeting disturbed skin and gut microbiota in Rosacea patients have been documented 25 .…”
Section: Introductionmentioning
confidence: 99%
“… 19 Studies have shown that cigarette smoking and drinking can affect the human microbiome, 20 , 21 and changes in skin microbiome and intestinal microbiome are closely related to the occurrence and development of Rosacea. 22 , 23 , 24 Effective treatment interventions targeting disturbed skin and gut microbiota in Rosacea patients have been documented. 25 However, the unclear pathophysiological mechanisms of Rosacea underscore the importance of understanding its risk factors for preventive strategies and further exploration of its underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%